Pengaruh Leverage, Kepemilikan Keluarga, Kualitas Audit Terhadap Tax Avoidance - Dewi Shintawati Kusnadi; Pandoyo (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
This study aims to obtain empirical evidence regarding the effect of leverage, family ownership, audit quality on tax avoidance. The population in this study are all real estate sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2018 to 2020. The sample determination uses a purposive sampling technique. The analytical technique used is Multiple Linear Regression. The test results show empirical evidence that 1) leverage has a negative and significant effect of 23.9 percent on tax avoidance, 2) family ownership has a positive and significant effect of 25.9 percent on tax avoidance, 3) audit quality has a negative and significant effect of 39.5 percent on tax avoidance, and 4) leverage, family ownership, and audit quality simultaneously have an effect of 40.9 percent on tax avoidance